Sludge Bed Granules’ Growth in the HUASB Reactor Treating High Strength Industrial Wastewater - Habeeb, Sinan Abood; Abdul Latiff, Ab. Aziz; Daud, Zawawi; Ahmad, Zulkifli (International Journal of Integrated Engineering, 2014)
The development of anaerobic sludge granules in a hybrid up-flow anaerobic sludge bed (HUASB) reactor in terms of granular size and solids content was observed. After appropriate pre-treatment of the palm oil mill effluent (POME), it was continuously fed to the HUASB reactor under room temperature condition (27°C). Particle size analysis and solids content examination were conducted for 196 days. A volatile solid ratio was ranging from 0.36 to 0.51 which was quite low, and granules particle size of less than 1 mm diameter was reported during the operating period. Results obtained in this study indicated that sludge bed development based on the sludge particle size distribution and the volatile solid ratio, was quite slow due to the bulk solids that entering the reactor resulting in certain inhibition of the anaerobes’ activity. It has been concluded that anaerobic wastewater treatment process in anaerobic reactors such as the HUASB reactor, can be significantly affected by the organic loading rate, hydraulic retention time applied to the reactor and the wastewater characteristics.